KONSEPSI PERENCANAAN ORGANISASI RUANG ISLAMI - Sri Puji Astuti (LPPM Universitas Pekalongan, 2014)
Public housing issue in Indonesia, particularly in the urban area, has become a widely discussed issue, whether related to land limitation, increasing price, or the developer promises that sometimes differ from the existing facts. Whatever the problem is, the housing requirements for the predominantly Moslem population should be the major consideration, before other aspects are considered. The fact is that this matter has been neglected due to the consideration of bigger people needs. Other than that, the highly increasing price should be reconsidered because it is related to purchasing power of the people. In other words, in the end, people do not always have an option to choose the best they think because at the same time they have to fulfill their basic needs. This writing attempts to provide an alternative concept that can be applied in creating a conducive housing for Moslem families. It is expected that this concept can be applied in the general housing planning. Key words: rooms, housing, Moslem